Building a better team a handbook for managers and facilitators - Moxon, Peter (Gower, 1993)
Team leadership and team development are central to the modern manager's ability to "achieve results through other people". Successful team-building requires knowledge and skill, and the aim of this handbook is to provide both. Using a blend of concepts, practical guidance and exercises, the author explains the how and why of team development. Drawing on his experience as a manager and consultant, he describes how groups develop, how trust and openness can be encouraged, and the likely problems to be overcome. Detailed advice on the planning and running of team-building programmes, and a series of activities, which include necessary instructions and support materials are also contained in this guide. It is designed for managers, trainers and consultants.